Comparative Study on the Effect of Polyvinylpyrrolidone (PVP K30) Concentration on the Structure and Performance of Chitosan Membranes for Phosphate Ion Filtration - Retno Ariadi Lusiana; M. Ridho Shofwan Al Aziz; Didik Setiyo Widodo; Khabibi Khabibi (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2025)
The increasing concentration of phosphate in industrial and agricultural waste is a major cause of eutrophication, which threatens the balance of aquatic ecosystems. Membrane technology offers an effective approach for phosphate ion removal through the combined mechanisms of filtration and adsorption. In this study, chitosan membranes were modified with polyvinylpyrrolidone K30 (PVP K30) at four different concentrations using the phase inversion method. Increasing the PVP K30 content in the chitosan membrane enhanced water absorption, porosity, and hydrophilicity. These improvements significantly influenced phosphate ion filtration performance, resulting in a flux increase of 33–48% and an enhancement in phosphate ion rejection of 32–39% compared to the unmodified chitosan membrane. Furthermore, phosphate ion adsorption on the membrane surface was observed, which is likely attributed to the presence of surface functional groups with different charges and to membrane pore sizes comparable to the size of phosphate ions.